Searching for trends in mesopause region airglow intensities and temperatures at El Leoncito - Reisin, Esteban Rodolfo (2002)
Using our large data base from the Argentine site at El Leoncito that covers the years from August 1997 to May 2001, and four individual campaigns in 1986, 1987, and 1992, we search for trends in temperatures corresponding to heights of 87 and 95 km. Also the variations in OH and O2 airglow band intensities for these two altitudes supply complimentary information interesting in terms of trends. The seasonal variation is well documented with good reproducibility, since the end of a perturbation possibly due to the 1997 ENSO event, so that the time series of nocturnal mean values can be reliably freed from the seasonal effect. Some difficulties arise from the geophysical variations (mostly from planetary waves) still present in the data averages over 28 nights of observation. In spite of this, temperature trends of a fraction of 1 K/year should be detectable, using only the data from 1998 to 2001. However, only at 95 km, there is a significant positive temperature trend over the last 4 year. When the earlier campaigns are included, this 15 year data span shows a negative temperature trend of about )1 K/year and a positive (OH) intensity trend of about +1%/year, at 87 km. At 95 km, there is a similar (O2) intensity trend, but a temperature trend compatible with zero. These results are similar to previous findings for Northern Hemisphere midlatitude sites, by other investigators. As a by-product of the trend analysis, we also estimate values for the 1997 ENSO temperature anomaly of about )3.5 K at 87 km, and )6 K at 95 km.